Meninjau Ulang Strategi Membaca: English - Prasetia, Ade; Dwiniasih, Dwiniasih; Pradeska, Nelan Bahar (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
Reading comprehension remains a persistent challenge for Indonesian high school students, as evidenced by the country's below-average performance in international assessments like PISA. This issue is particularly evident in understanding news item texts, which require critical thinking and text-structure awareness. The present study investigates the effectiveness of the SQ3R technique—Survey, Question, Read, Recite, and Review—in improving students' comprehension of news item texts. Using a pre-test and post-test design with 34 Grade XI students, the results revealed a significant improvement in comprehension, with mean scores increasing from 61.47 to 81.91. The t-test analysis indicated a statistically significant difference (p < 0.05), confirming the effectiveness of the technique. The findings underscore the potential of SQ3R in enhancing comprehension through structured, sequential reading stages. Recommendations include integrating SQ3R into reading curricula and providing additional support for students struggling with text structure and vocabulary.